2017
DOI: 10.7326/m17-0882
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Subclinical Primary Aldosteronism and Incident Hypertension

Abstract: Background Primary aldosteronism is recognized as a severe form of “renin-independent aldosteronism” that results in excessive mineralocorticoid receptor (MR) activation. Objective To investigate whether there is a spectrum of subclinical renin-independent aldosteronism among normotensives that increases risk for hypertension. Design Cohort study. Setting National community-based study. Participants 850 untreated normotensive participants in the Multi-Ethnic Study of Atherosclerosis with measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 51 publications
7
106
0
3
Order By: Relevance
“…Second, participants were classified into 3 categories of PRA of ≤0.50, 0.51 to 0.99, and ≥1.0 μg/L per hour, to characterize “suppressed renin phenotype (a state of autonomous aldosterone production),” “indeterminate renin phenotype,” and “unsuppressed renin phenotype” (a state of potentially appropriate mineralocorticoid receptor activation in the setting of physiologic renin‐dependent secretion of aldosterone). The referent category (≥1.0 μg/L per hour) was compared with the 0.51 to 0.99 and ≤0.50 μg/L per hour categories for the association with incident diabetes mellitus 9. Third, participants were classified into 3 categories of PRA of ≤0.50, 0.51 to 0.99, and ≥1.0 μg/L per hour and the association of log‐aldosterone with incident diabetes mellitus was assessed among participants in the 3 PRA classifications 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, participants were classified into 3 categories of PRA of ≤0.50, 0.51 to 0.99, and ≥1.0 μg/L per hour, to characterize “suppressed renin phenotype (a state of autonomous aldosterone production),” “indeterminate renin phenotype,” and “unsuppressed renin phenotype” (a state of potentially appropriate mineralocorticoid receptor activation in the setting of physiologic renin‐dependent secretion of aldosterone). The referent category (≥1.0 μg/L per hour) was compared with the 0.51 to 0.99 and ≤0.50 μg/L per hour categories for the association with incident diabetes mellitus 9. Third, participants were classified into 3 categories of PRA of ≤0.50, 0.51 to 0.99, and ≥1.0 μg/L per hour and the association of log‐aldosterone with incident diabetes mellitus was assessed among participants in the 3 PRA classifications 9…”
Section: Methodsmentioning
confidence: 99%
“…Among blacks in the Jackson Heart Study,6 aldosterone was positively associated with insulin resistance, while higher levels of aldosterone across the spectrum were associated with a dose‐dependent higher risk of the development of type 2 diabetes mellitus over 8 years. Recent observations demonstrate that aldosterone can be produced autonomously from aldosterone producing cell clusters within morphologically normal adrenal glands with a large spectrum and high prevalence of subclinical aldosteronism 7, 8, 9. Thus, we examined the association of aldosterone and PRA with glucose metabolism and incident diabetes mellitus across the spectrum of aldosterone levels in a multiethnic cohort to determine if there are racial/ethnic differences.…”
Section: Introductionmentioning
confidence: 99%
“…In another study 60 61 Furthermore, only when renin was suppressed, high aldosterone levels were associated with an increased risk for incident hypertension. 61 The increase in aldosterone secretion, that progressively becomes independent from angiotensin II regulation, results in normotensive aldosteronism. According with a recent study conducted on a cohort of predominantly female individuals, normotensive aldosteronism can be detected (by postfludrocortisone-dexamethasone suppression test) in 13% of the participants.…”
Section: Subclinical Primary Aldosteronismmentioning
confidence: 95%
“…Similarly, a prospective longitudinal study recently demonstrated that normotensive individuals with suppressed renin activity (≤0.50 μg/L/h, independently from aldosterone status), display a higher risk of developing hypertension compared with patients with unsuppressed renin phenotype . Furthermore, only when renin was suppressed, high aldosterone levels were associated with an increased risk for incident hypertension . The increase in aldosterone secretion, that progressively becomes independent from angiotensin II regulation, results in normotensive aldosteronism.…”
Section: Primary Aldosteronismmentioning
confidence: 98%
See 1 more Smart Citation